An Analysis of Morphological Errors in Arabic Writing Skills of Third-Semester Students at Nahdlatul Ulama University Yogyakarta / Analisis Kesalahan Morfologis dalam Keterampilan Menulis Mahasiswa Semester III di Universitas Nahdlatul Ulama Yogyakarta - Uswatun Hasanah; Mohammad Rofiqi; Muhammad Jafar Shodiq; Nur Hidayah (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2026)
Mastering Arabic writing skills (Mahārat al-Kitābah) requires strong morphological competence because it underlies accurate word formation and meaning. Yet, morphological errors still frequently appear and influence students’ writing performance. This study analyzes the types of morphological errors in the Arabic writing of third-semester students at Nahdlatul Ulama University Yogyakarta and identifies the factors causing them. Using a qualitative error-analysis approach, the research draws on students’ written assignments as the main data source. The findings show four major error categories: verb conjugation, plural formation, verb–pronoun mismatch, and gender agreement. These errors are mainly caused by limited understanding of ṣarf, Indonesian language interference, and insufficient structured writing practice. The results underline the need for teaching strategies that improve accuracy in Arabic writing.Menguasai keterampilan menulis bahasa Arab (Mahārat al-Kitābah) memerlukan kompetensi morfologis yang kuat karena hal ini mendasari pembentukan kata dan makna yang akurat. Namun, kesalahan morfologis masih sering muncul dan mempengaruhi kinerja menulis mahasiswa. Studi ini menganalisis jenis-jenis kesalahan morfologis dalam tulisan bahasa Arab mahasiswa semester tiga di Universitas Nahdlatul Ulama Yogyakarta dan mengidentifikasi faktor-faktor penyebabnya. Menggunakan pendekatan analisis kesalahan kualitatif, penelitian ini mengandalkan tugas tertulis mahasiswa sebagai sumber data utama. Temuan menunjukkan empat kategori kesalahan utama: konjugasi kata kerja, pembentukan jamak, ketidakcocokan kata kerja–kata ganti, dan kesesuaian gender. Kesalahan-kesalahan ini terutama disebabkan oleh pemahaman yang terbatas tentang ṣarf, interferensi bahasa Indonesia, dan kurangnya praktik menulis yang terstruktur. Hasilnya menekankan perlunya strategi pengajaran yang meningkatkan akurasi dalam penulisan bahasa Arab.